STRATEGI KOMUNIKASI VISUAL EDUKASI INSECURITY SEBAGAI DAMPAK PENGGUNAAN MEDIA SOSIAL PADA REMAJA PEREMPUAN - Anny Valentina; Grivenna Lavender Putri; Valiani Valiani; Olivia Halim Putri (Jurnal Bahasa Rupa, 2022)
The widespread use of social media among adolescent can have both positive and negative impacts. Insecurity is most impact that often felt by adolescent when exposed to too much by social media. They will be comparing themselves to others who look perfect on social media. If the perfect standard of social media is not achieved, then teenagers will tend to feel like a failure. If this is not immediately communicated, it will harm for the psyche and mentality. At the pre-research stage, it was found that by discovering the strengths of adolescent, it should be a motivation for self-development. So, it is necessary to find out visual communication that can be recommended to provide education to teenagers to find their potential so that they avoid insecurity. The purpose of this research is to find recommendations for visual communication that can be used to provide education about insecurity by adopting the consumer path 5A strategy and doing mind mapping in developing creative concepts. The method used in this research is qualitative by conducting observations and literature studies at the pre-research stage, followed by data collection by surveys, and focus group interviews on adolescent girls aged 18-21 years. This interview was carried out virtually because the current situation did not allow direct or face-to-face interviews. The results of this study are Instagram can be used as a communication medium and visual communication by providing motivation to carry out self-development can used as an alternative education through visual communication to help teenage girls aged 18-21 years to avoid insecurity.